2005
DOI: 10.2174/1570162053506964
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Care of the HIV Infected Patient in the Highly Active Antiretroviral Therapy (HAART) Era

Abstract: The inpatient presentation of the HIV infected patient has changed over the years. From the early years when patients presented with accumulating opportunistic infections that led to an early demise to the HAART era with reports of dramatic decreases in opportunistic infections and improvements in life expectancy, the evolution of inpatient HIV care has been a challenge to the clinician. In the HAART era the presentation of the HIV inpatient has diversified and in many ways is more challenging than the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 75 publications
0
5
0
2
Order By: Relevance
“…At the same time, given the association of increased viral load with ED utilization, it is also likely that these ill-defined symptoms/signs represent patient complaints that are potentially related to poor control of their underlying systemic infection or side effects from complex medication regimens. Other studies have found that hospitalizations specifically related to medication side effects have increased in the HAART era [4, 5]. The use of ICD-9 coding and classification would not easily allow examination of whether particular diagnoses were related to HAART regimens or not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, given the association of increased viral load with ED utilization, it is also likely that these ill-defined symptoms/signs represent patient complaints that are potentially related to poor control of their underlying systemic infection or side effects from complex medication regimens. Other studies have found that hospitalizations specifically related to medication side effects have increased in the HAART era [4, 5]. The use of ICD-9 coding and classification would not easily allow examination of whether particular diagnoses were related to HAART regimens or not.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in life expectancy, largely attributable to HAART [3], has also resulted in a changing spectrum of illness for HIV-positive adults. Recent studies from the HAART era where patients have access to such medications have found that hospitalizations due to opportunistic infections, especially late-stage conditions such as Cryptosporidium and Mycobacterium avium , have decreased while those related to cardiovascular disease, medication side effects, and malignancies have increased [4, 5]. This pattern stands in contrast to the pre-HAART era when opportunistic infections comprised over 23% of hospital discharge diagnoses, with an additional 10.1% due to respiratory ailments, predominantly pneumonia of an uncharacterized nature [6].…”
Section: Introductionmentioning
confidence: 99%
“…La puntuación global de la ECSP permite clasificar la calidad del sueño en cuatro categorías: buena calidad de sueño (≤ 5), mala calidad del sueño leve (6)(7)(8), mala calidad del sueño moderada (9-11) y mala calidad del sueño severa (> 11) 42,43,44 . Sin embargo, para el análisis de la asociación con la adherencia al TARGA, las malas calidad del sueño moderada y severa fueron incluidas en la misma categoría, puesto que en ambos casos se requiere de evaluación médica especializada 43 .…”
Section: • Aspectos Clínicosunclassified
“…El control, manejo y prevención de esta enfermedad requiere una importante inversión de recursos públicos para su prevención, control y tratamiento, especialmente en países de ingresos bajos o medianos 6 . El tratamiento antirretroviral de gran actividad (TARGA) es una de las más importantes medidas para evitar las enfermedades oportunistas y las muertes asociadas 3,7,8,9,10 .…”
Section: Introductionunclassified
“…[8] HIVinfected patient care has now shifted from complications arising from opportunistic infections to other causes attributable to HIV pathogenesis and toxic effects of HAART. [9] Studies have shown a significant reduction in mortality of HIV-infected individuals for the post-HAART era as compared with pre-HAART era. [6] Recent studies have demonstrated that HAART may not be helpful in controlling the virus replication after the acute infection has suppressed the lymphoid system.…”
Section: Hiv and Haartmentioning
confidence: 99%